2005
DOI: 10.1111/j.1471-4159.2005.03454.x
|View full text |Cite
|
Sign up to set email alerts
|

Post‐training intrahippocampal infusion of nicotine prevents spatial memory retention deficits induced by the cyclo‐oxygenase‐2‐specific inhibitor celecoxib in rats

Abstract: Recently, we demonstrated that intrahippocampal infusion of the cyclo-oxygenase (COX)-2-specific inhibitor celecoxib impaired spatial memory retention in the Morris water maze. In the present work, we investigated the effects of nicotine, infused in the rat dorsal hippocampus several minutes after infusion of celecoxib, on memory retention in the Morris water maze. Rats were trained for 3 days; each day included two blocks, and each block contained four trials. Test trials were conducted 48 h after surgery. As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 98 publications
(117 reference statements)
4
29
0
Order By: Relevance
“…However, the brain region(s) through which nicotine produces its effect on the task could not be identified from the results of the study, because systemic administration of nicotine and DH␤E will, by definition, result in the action of the drugs throughout the central and peripheral nervous systems. Thus, the results of the present research significantly extend the findings of Davis and Gould (2006) and the findings from previous studies indicating that nicotine enhances hippocampus-dependent learning and memory (Buccafusco et al, 1996;Levin et al, 1997;Gould and Wehner, 1999;Barros et al, 2004;Sharifzadeh et al, 2005) by directly demonstrating that DH␤E-sensitive nAChRs in the hippocampus are critical for the enhancing effect of the drug. DH␤E antagonizes nAChR subtypes, including ␣4␤2, ␣4␤4, ␣3␤2, ␣2␤2, and ␣2␤4 nAChRs, that bind nicotine with high affinity (Harvey et al, 1996;Khiroug et al, 2004).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…However, the brain region(s) through which nicotine produces its effect on the task could not be identified from the results of the study, because systemic administration of nicotine and DH␤E will, by definition, result in the action of the drugs throughout the central and peripheral nervous systems. Thus, the results of the present research significantly extend the findings of Davis and Gould (2006) and the findings from previous studies indicating that nicotine enhances hippocampus-dependent learning and memory (Buccafusco et al, 1996;Levin et al, 1997;Gould and Wehner, 1999;Barros et al, 2004;Sharifzadeh et al, 2005) by directly demonstrating that DH␤E-sensitive nAChRs in the hippocampus are critical for the enhancing effect of the drug. DH␤E antagonizes nAChR subtypes, including ␣4␤2, ␣4␤4, ␣3␤2, ␣2␤2, and ␣2␤4 nAChRs, that bind nicotine with high affinity (Harvey et al, 1996;Khiroug et al, 2004).…”
Section: Discussionsupporting
confidence: 80%
“…However, the role of hippocampal nAChRs in the effect of acute nicotine on learning and memory has not been demonstrated directly. Equivocal results from previous studies (Barros et al, 2004;Sharifzadeh et al, 2005) indicate that the action of nicotine at hippocampal nAChRs may be sufficient to enhance learning and memory. But, it is not known whether the action of nicotine at hippocampal nAChRs is necessary for the enhancement of learning and memory.…”
Section: Introductionmentioning
confidence: 89%
“…1 ). These results are similar to those obtained in our previous studies [22,[25][26][27] . Posttraining bilateral infusions of H-89 (2.5 and 5 mol/l) into the CA1 region of the hippocampus caused significant increase in escape latency ( * * * p !…”
Section: Comparison Of Effects Of H-89 Dmso and Saline On Time And Dsupporting
confidence: 83%
“…We found that bilateral intrahippocampal infusion of DMSO did not induce any significant differences in escape latency, traveled distance and swimming speed, compared with saline-treated rats during the test trials. The effective use of DMSO as a vehicle has also been reported in our previous work [22,[25][26][27] . Therefore, it appears here that DMSO infusions did not cause motor disturbances or have significant effects on spatial memory parameters.…”
Section: Discussionmentioning
confidence: 86%
“…In agreement with human studies, there is a great body of evidence suggesting that acute nicotine augments hippocampus-dependent contextual and spatial learning and memory while not affecting hippocampus-independent subtypes of learning (e.g., cued learning) in rodents. For example, numerous studies from both our group and other laboratories showed that acute nicotine enhanced hippocampus-dependent contextual and trace fear conditioning, but not cued fear conditioning (Gould and Wehner 1999;Gould and Higgins 2003;Gould 2003a;Gould and Lommock 2003;Gould et al 2004;Wehner et al 2004;Gould 2006, 2007;Raybuck and Gould 2007;Gulick and Gould 2008;Kenney and Gould 2008;Tian et al 2011;Portugal et al 2012a, b), as well as spatial object recognition (Kenney et al 2011), spatial learning and memory in Morris water maze (Abdulla et al 1996;Sharifzadeh et al 2005), and spatial working memory in radial arm maze tasks (Levin and Torry 1996;Levin et al 1997Levin et al , 1998. It is possible that the formation of nicotine-context associations may benefit from these procognitive effects of acute nicotine.…”
Section: Nicotinementioning
confidence: 91%